A simple method for evaluating the sustainable design of energy efficient family houses - Praznik, Miha (Strojniški vestnik, 2014)
Buildings have negative effects on the environment throughout their life cycle, i.e. from the phase of obtaining raw materials and manufacturing materials and components up to the sale, building and use through the final phase of removal when the building is decommissioned. In general, current legislation limits both the use of energy and the emissions allowed during operation, but does not limit the other parameters that define the design of contemporary sustainable buildings. Determining the sustainability of buildings should take place in the planning phase of the project, when it is still possible to influence the outcome. In this article, a simplified method using five chosen indicators is employed to evaluate the level of sustainability. The areas to be evaluated are energy efficiency, use of primary energy, CO2 emissions, costs, and the level of living comfort achieved. The evaluation using these indicators is carried out using three subjective and objective weighting methods, such that the final evaluation includes the viewpoints of an independent evaluator and the points of view of both the user and the state. In the case of an assessment of the five indicators for new constructions, it is ensured that the designs for the new building in energy class A have the best total result of the assessment and therefore the best sustainable design, regardless of additional energy, environmental and economic investment during the building phase. With a suitable choice of heat supply, even new buildings in energy class C can come close to the effectiveness of a building design in energy class B.
Keywords: bivalno okolje; emisije CO2; energijska učinkovitost; enodružinske stavbe; enostavne metode; ocena učinkovitosti; raba primarne energije; stroški; trajnost